Letter by Rodriguez-Granillo et al Regarding Article, "Acute Myocardial Infarction: Changes in Patient Characteristics, Management, and 6-Month Outcomes Over a Period of 20 Years in the FAST-MI Program (French Registry of Acute ST-Elevation or Non-ST-Elevation Myocardial Infarction) 1995 to 2015" - Rodriguez Granillo, Gaston Alfredo (2018)
We have read with interest the study by Puymirat et al1 updating the management and mortality data of patients with ST-segment–elevation myocardial infarction by using nationwide French registries 5 years apart from 1995 to 2015. The authors reported stable improvements in several variables, including time from symptom onset to hospital admission, use of mobile intensive care units, rates of reperfusion therapy, and more frequent use of primary percutaneous coronary intervention, and of antiplatelet and anticoagulant agents, as well. Overall, this has led to a consistent decrease of in-hospital and 6-month mortality rates over time. However, the burden of reduction in the rates of death progressively declined in the past decade, and were marginal (particularly among patients with non–ST-segment–elevation myocardial infarction) between 2010 and 2015.